Preference Government Regulation No 23 of 2018 with General Income Tax Scheme - Nufera L D; I N Darmayasa; I N Mandia (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
This study aims to comparing between Government Regulation No. 23 of 2018 (PP 23) with the general income tax scheme to find out the most appropriate and profitable method for Small and Medium Enterprise. This research used qualitative analysis technique. Data is collected through interviews with entity owner, tax consultant, and tax academic. The informant's perspective that PP 23 is fair, optional, and educational. Taxpayers prefer to use PP 23 because it’s simpler than the general scheme, even though making it a higher tax payment. The preference of informants related to PP 23 is more profitable than PP 46. Consultant and tax academic believe that PP 23 can improve tax compliance. There are concerns that taxpayers who prioritize rationality will use policy loopholes to develop aggressive tax planning. This finding is an alternative to legal tax planning and as an alternative to making tax policies to encourage small and medium enterprises. This research has some novelty, PP 23 is a substitute policy of PP 46 believed to be more fair and hasn’t been widely studied, this research using qualitative method refers to comparative to complementing previous research, and research contributions are very useful for taxpayer education that are in line with the government's program to increase the small and medium enterprise class.